2017
DOI: 10.1007/s00415-017-8701-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the yield of 24-h close observation in patients with mild traumatic brain injury on anticoagulation therapy: a retrospective multicenter study and meta-analysis

Abstract: Delayed (diagnosis of) ICH within 24 h is very rare in mTBI patients on anticoagulants after reportedly normal initial CT. Routine hospitalization of these patients seems unwarranted when the initial cranial CT is scrupulously evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…In adults, observation has been shown to be as effective as the CT in the presence of a caregiver and a patient able to understand home instructions [ 46 ]. Our results show similar percentages of positive second CTs of the brain as previous studies [ 20 , 43 , 46 , 59 , 62 , 63 , 64 , 65 , 66 ]. In addition, even our patients who tested positive for the second CTs did not require surgery, as another study showed.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In adults, observation has been shown to be as effective as the CT in the presence of a caregiver and a patient able to understand home instructions [ 46 ]. Our results show similar percentages of positive second CTs of the brain as previous studies [ 20 , 43 , 46 , 59 , 62 , 63 , 64 , 65 , 66 ]. In addition, even our patients who tested positive for the second CTs did not require surgery, as another study showed.…”
Section: Discussionsupporting
confidence: 91%
“…In our observation, the rate of delayed hemorrhage was relatively low. We, therefore, with some prudence, align with other authors that suggest that patients presenting with a negative first CT scan and without neurological deterioration can be safely discharged after a short period of in-ward observation with a low rate of complications and without a second CT scan [ 20 , 43 , 46 , 59 , 62 , 63 , 64 , 65 , 66 ]. We also think that this could apply especially to patients on DOAC.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is the first meta‐analysis to address this question. Two recent meta‐analyses reported a very low rate of delayed ICH in anticoagulated head injured patients with a normal head CT scan (Chauny et al , ; Verschoof et al , ). These meta‐analyses did not report on the incidence of ICH at evaluation in the ED.…”
Section: Discussionmentioning
confidence: 99%